The association between the composition of the early-life intestinal microbiome and eczema in the first year of life - Leo, Stefano; Cetiner, Omer Faruk; Pittet, Laure F.; Messina, Nicole L.; Jakob, William; Falquet, Laurent; Curtis, Nigel; Zimmermann, Petra (Frontiers in Microbiomes, 2023)
Introduction: The early-life intestinal microbiome plays a crucial role in the development and regulation of the immune system. Perturbations in its composition during this critical period have been linked to the development of allergic diseases. Objective: To investigate the association between the composition of the early-life intestinal microbiome and presence of eczema in the first year of life using shotgun metagenomics sequencing and functional analyses (metabolic pathways). Methods: Stool samples from 393 healthy term-infants collected at one week of age were analysed with shotgun metagenomics sequencing. Environmental and clinical data was prospectively collected using 3-monthly validated questionnaires. Participants were clinically assessed during study visits at 12 months of age. Eczema was diagnosed by the UK diagnostic tool and by a research nurse. Data analysis was stratified by delivery mode. Results: Eczema was diagnosed in 16.4% (60/366) by nurse diagnosis. Infants born by Caesarean section-(CS) with nurse-diagnosed eczema had higher relative abundance of Escherichia, Shigella, Enterobacter and Citrobacter and lower relative abundance of Veillonella compared to CS-born infants without eczema. The latter had a higher abundance of genes involved in lactic fermentation. Vaginally-born infants with eczema had a higher relative abundance of Bacteroides and lower abundance of Streptococcus. Conclusion: There is an association between the bacterial composition of the intestinal microbiome at one week of age and the presence of eczema in the first 12 months of life.